Aberrant regeneration of the third cranial nerve - Shrestha, UD; Adhikari, S (Nepalese Journal of Ophthalmology, 2012)
Background: Aberrant regeneration of the third cranial nerve is most commonly due to its damage by trauma. Case: A ten-month old child presented with the history of a fall from a four-storey building. She developed traumatic third nerve palsy and eventually the clinical features of aberrant regeneration of the third cranial nerve. The adduction of the eye improved over time. She was advised for patching for the strabismic amblyopia as well. Conclusion: Traumatic third nerve palsy may result in aberrant regeneration of the third cranial nerve. In younger patients, motility of the eye in different gazes may improve over time. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5872 NEPJOPH 2012; 4(1): 176-178